Analisis Fenomena Flypaper Effect pada Belanja Daerah dengan Pendekatan Software SPSS 20: Analysis of the Flypaper Effect Phenomenon on Regional Spending with the SPSS 20 Software Approach - Nauw, Ester Trivona; Asyik, Nur Fadjrih; Riharjo, Ikhsan Budi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
The purpose of this study is to identify and understand how Local Revenue, General Allocation Fund, and Special Allocation Fund affect Regional Expenditure, and to explore the Flypaper Effect Phenomenon in districts/cities in West Papua during the 2016-2020 period. The population studied included districts/cities in West Papua Province with a sample consisting of 13 entities. The data used came from the Budget Realization Report (LRA) issued by the Directorate General of Fiscal Balance for all districts/cities. The research sample was obtained through a total sampling technique. This study uses a multiple linear regression analysis method. The results of the study indicate that Local Revenue, General Allocation Fund, and Special Allocation Fund have a positive influence on Regional Expenditure, and the Flypaper Effect Phenomenon was detected in district/city governments in West Papua.